Development of the magnetic separation device for surface cracks of delinted cottonseed - Du, Xinwu; Wang, Guodong; Pang, Jing; Li, Pengfei; Jin, Xin; Mao, Wenhua (International Journal of Agricultural and Biological Engineering, 2024)
In seed processing for commercial production, the collision or friction between mechanical parts and seed is inevitable. These collisions or friction can cause cracks on the surface of the seed, which can affect germination rates and ultimately reduce crop yields. Using the difference of the seed motion trajectories with different crack degrees in the magnetic field, the grading of the surface crack seed can be realized. In this study, the motion law of seed in a non-uniform magnetic field was analyzed by taking the delinted cottonseed as an object. A magnetic separation device for crop seeds was developed. This device was essentially composed of the feed throat, magnetic roller, conveyor belt, and variable-frequency adjustable-speed motor. The magnetic powder adhering seeds enter the magnetic separation device through the feed throat and are conveyed to the magnetic roller through the conveyor belt. The magnetic roller has different adsorption forces on seeds with different degrees of cracking, and seeds fall into different outlets, thus completing the grading of the seeds. By adjusting working parameters such as the magnetic field strength and the speed of the conveyor belt, magnetic separation could be made. In order to verify the grading effect, the magnetic separation accuracy was taken as the inspection index, the magnetic powder’s mesh number, the mass mixing ratio between magnetic powder and delinted cottonseed, and the rotation speed of the magnetic roller were taken as the inspection factors. The response surface methodology was used to optimize the working parameters of the experimental device. The results showed that the optimal process parameters of the magnetic separation device were as follows: the number of magnetic powder meshes was 250, the mass mixing ratio between magnetic powder and delinted cottonseed was 1:20, and when the rotational speed of the magnetic separation roller was 20 r/min, the detection rate reached 92.5%. The designed magnetic separation device can realize the non-destructive batch detection of seed surface cracks with high work efficiency and has guiding significance for the high-precision and low-damage classification detection and classification of commercial seed. Keywords: magnetic separation; delinted cottonseed; surface crack; response surface design DOI: 10.25165/j.ijabe.20231606.7509 Citation: Du X W, Wang G D, Pang J, Li P F, Jin X, Mao W H. Development of the magnetic separation device for surface cracks of delinted cottonseed. Int J Agric & Biol Eng, 16(6): 11-19.